An Aboriginal English Ontology Framework for Patient-Practitioner Interview Encounters - Forbes, David; Sidhu, Amandeep; Singh, Jaipal (IEEE, 2010)
Current diagnosis, treatment and healthcare delivery processes in Australia are dominated by long established westernized clinically driven methods of patient-practitioner interaction. Consequently this dominant healthcare provider influence contributes to risk of miscommunication, misinformation in patient records and reciprocal misunderstandings that go unrecognised as such. For Indigenous communities, inadequate health literacy (HL) and a pervasive semantic disconnect are major barriers. Overcoming these barriers in the primary care setting presents opportunities to deliver appropriate timely and more effective care. We propose an e-health framework that enhances the Patient-Practitioner Interview Encounter (PPIE) through the use of a patient-centric linguistic interface using semantic mappings between Aboriginal English (AE) and Standard Australian English (SAE). This will ameliorate communications and interactions, so meeting the needs of all stakeholders (Patients, Physicians, Nurses, Allied Health Professionals and their Non-Critical Carers) engaged in Indigenous patient-centric primary care. It provides healthcare practitioners and their Indigenous T2DM patients with a new platform for two-way educative sharing and knowledge exchange that will increase mutually productive treatment, care and management expectations.